‘Unprofitable Reading’ of the Pechora Peasants - Волкова, Татьяна (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
In the paper the characteristics of plot and composition of the rhymed ‘Tale about a merchant and his sly wife’ are analyzed. The study is based on a manuscript from the Lower Pechora, preserved in the Ust-Tsilem collection of the Pushkin House. Originality of the Pechora variant is shown in comparison with the verse facetiae on a similar theme published by A.V. Kokorev in 1941.